Dietary and lifestyle oxidative balance scores and their impact on cardiovascular diseases: exploring the mediating influence of hepatic function and blood lipid levels - He, Yi; Lan, Ying (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLimited evidence exists regarding the association between oxidative stress induced by dietary and lifestyle factors and cardiovascular diseases (CVDs).MethodsWe conducted a weighted analysis using data from 13,530 adults in the National Health and Nutrition Examination Survey (NHANES), covering the period from 2003 to 2018. The total oxidative balance score (OBS) was derived from 20 oxidative stress-related exposures, including dietary and lifestyle factors. Survey-weighted multivariable logistic regression and stratified analyses were performed to examine the association between OBS and CVDs. To further investigate the nonlinear relationship, we employed restricted cubic spline analysis and threshold effect analysis. Additionally, we assessed whether hepatic function and blood lipid levels mediate the OBS-CVDs relationship.ResultsThis study included 13,530 participants, representing a weighted population of 81,006,649.2 individuals. After adjusting for potential confounders, a linear relationship was observed between total OBS, dietary OBS, and CVDs, while lifestyle OBS exhibited a nonlinear association, with a significant threshold effect at a score of 4. When the lifestyle OBS exceeded this threshold, a marked negative correlation with CVDs was observed. Furthermore, albumin (Alb) mediated 23.59% of the relationship between the total OBS and CVDs.ConclusionsLower levels of total OBS were inversely associated with CVDs. This association was partially mediated by blood lipid levels and hepatic function. Interventions focusing on antioxidant-rich dietary and lifestyle modifications may play a pivotal role in reducing the possibility of CVDs.